CELEBRATIONS FOR THE FIRST CENTURY OF THE CONSUMPTION OF INDEPENDENCE, NEW IMPULSE OR THE SOCIAL CATHOLICISM (Tzintzun, Revista de Estudios Históricos, 2016)
On September 1910, it was celebrated the first century of the independence, apotheosis of Díaz, monthslater the revolution was broken out. With the Plan de San Luis, Mexico had certain political and peacestability, celebrating the century of the consumption on 1921 independence, where several socialgroups manifested. Mexican Catholic Church was not alien to the actions related to this historicalfact, rescuing its presence. The Mexican revolution, with Madero, was well spent by social Catholicsto set up a political party that added itself to the trade unions, saving banks, schools and catholic pressthat recovered part of their old favorable conditions. For Catholics, the death of Madero and thepresence of Carranza were both a hard time, stopping their projects as well as the expulsion from thecountry of several of their leaders, but the organizations’ plans survived. At the early 20´s socialCatholicism emerged and with it returned the exiled Catholics and gathered again. With the religioncelebrations and the celebrations of the century of the independence, spaces were taken by MexicanCatholic Church public giving a new impulse to their cause. In this paper, we consider the differentactions taken by radical social Catholics, as well as having a better vision of the celebrations of theconsumption of the independence in 1921.
Keywords: Social Catholicism; century of the independence consumption; Mexican Catholic Church